On a fully fuzzy framework for minimax mixed integer linear programming - Arana-Jiménez, Manuel; Blanco, Víctor (Computers & industrial engineering, 2019)
•A crisp multiobjective MILP formulation is proposed to solve the problem.•We extend the notion of maximum to fuzzy numbers by means of the minimal upper bound.•We provide equivalent formulations for fully fuzzy minimax mixed integer programs.•The methodology is applied to Center Capacitated Facility Location Problem. In this work, we present a modeling framework for minimax mixed 0–1 fuzzy linear problems. It is based on extending the usual rewriting of crisp minimax problems via auxiliary variables to model the maximum of a finite set of fuzzy linear functions. We prove that the considered problem can be equivalently formulated as a (crips) multiple objective mixed integer programming problem. The framework is applied to a fully fuzzy version of the capacitated center facility location problem.